A parallel-machine scheduling problem with two competing agents. Issue 6 (3rd June 2017) - Lee, Wen-Chiung; Chung, Yu-Hsiang; Wang, Jen-Ya
ABSTRACT: Scheduling with two competing agents has become popular in recent years. Most of the research has focused on single-machine problems. This article considers a parallel-machine problem, the objective of which is to minimize the total completion time of jobs from the first agent given that the maximum tardiness of jobs from the second agent cannot exceed an upper bound. The NP-hardness of this problem is also examined. A genetic algorithm equipped with local search is proposed to search for the near-optimal solution. Computational experiments are conducted to evaluate the proposed genetic algorithm.